2006
DOI: 10.2116/analsci.22.1571
|View full text |Cite
|
Sign up to set email alerts
|

Classification of the Binding Modes in Bovine Serum Albumin Using Terminally Substituted Alkane Analogues

Abstract: With the fluorescence probe of 8-anilino-1-naphthalenesulfonate (ANS), the binding modes of terminally substituted alkane analogues (CnX; X = COOH, OH, CHO, NH3, CONH2) to bovine serum albumin (BSA) were investigated using a competitive binding technique. The Scatchard plot of the fluorometric titration of BSA with ANS showed that the maximum binding number of ANS, nmax, was 3.81, with the binding constant, Kbnd, of 1.42 × 10 6 mol -1 dm 3 . The binding modes of CnX to BSA were analyzed based on the fluorometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
(27 reference statements)
0
9
0
Order By: Relevance
“…We previously reported the binding behavior of ANS to BSA, in which identical affinity for four ANS binding sites are expected by the Scatchard analysis. 21 The binding properties of the HSA and BSA have been frequently discussed on the assumption of their structural similarities because the three-dimensional structure was determined only for HSA. 27 However, attention should be paid to the small differences in their structures in discussing the correlation between structure and binding properties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported the binding behavior of ANS to BSA, in which identical affinity for four ANS binding sites are expected by the Scatchard analysis. 21 The binding properties of the HSA and BSA have been frequently discussed on the assumption of their structural similarities because the three-dimensional structure was determined only for HSA. 27 However, attention should be paid to the small differences in their structures in discussing the correlation between structure and binding properties.…”
Section: Resultsmentioning
confidence: 99%
“…19 In our previous studies, we demonstrated that terminallysubstituted alkanes (CnX) are useful model agents for studying the binding properties of biologically active hydrophobic agents on proteins, because the hydrophobicity and charge of CnX can be controlled by the alkyl-chain length (n) and the terminal unit (X), respectively. 20,21 In the present study, we examined the effects of CnX (X = OH, COOH, CHO and NH2) on the fluorescence intensity of the ANS bound to HSA. We also examined the effect of CnX on the fluorescence intensity of Trp-HSA.…”
Section: Introductionmentioning
confidence: 99%
“…10 Previous studies on simple Keggin structured POMs highlight the fact that they do interact with biological moieties such as proteins, for example forming 1 : 1 stoichiometric compounds with serum albumin, 11 in contrast with substituted alkanes, where three binding modes have been found. 12 Other work monitoring the interaction with human serum albumin has also uncovered the presence of two binding sites for POMs. 13 In this paper, we make use of the POM europium decatungstate, which has previously been incorporated into microheterogeneous media, 14-19 and report the effect of a simple protein, bovine serum albumin (BSA) on its luminescence.…”
Section: Introductionmentioning
confidence: 99%
“…In spite that other techniques, as well as other treatments of fluorescence data, indicate that a BSA molecule frequently can bind several solute molecules , the results obtained by the double logarithm approach consistently would indicate that n = 1 and hence that there is only a single binding site per protein . In fact, this is also the conclusion for practically all (more than 99%) of the works using BSA.…”
Section: Resultsmentioning
confidence: 86%